Local fruits wastes as a potential crop fertilizer / Mas Idayu Ahmad - Ahmad, Mas Idayu (2018)
Malaysia is one of the largest fruit producers in Asia which make fruits stalls or vendors can be easily found almost in all streets in Malaysia. However, only inner parts of the flesh are savored by the community, while the nutrient-rich peels are often discarded and neglected. This study aim to investigate the nitrogen, phosphorus and potassium level in four selected fruits peels, which are guava, papaya, watermelon and pineapple, and to evaluate the potential of those selected fruits peels as an amendment for plant growth. Dried peels were tested for nitrogen, phosphorus and potassium level by using kjeldahl method and atomic absorption spectroscopy respectively. Fruits peels fertilizer together with other treatment, chemical fertilizer, was amended to plants (Brassica sp.) and the growth was observed until they mature. The results showed that number of leaves, length of leaves and height of plants treated with chemical fertilizer were respectively 9.20 ± 0.45, 9.46 ± 0.66 cm and 15.88 ± 0.91 cm, followed by fruits peels 9.20 ± 0.45, 8.98 ± 0.69 cm and 13.68 ± 0.58 cm and control with 7.00 ± 0.71, 5.12 ± 0.61 cm and 9.92 ± 1.09 cm respectively. As for nitrogen, phosphorus and potassium level obtained were 22 mg/g, 10.3 mg/g and 13.9 mg/g respectively. These results proved that fruits peels can be used as an alternative organic-cost-saving source for soil amendment.